THE ROLE OF KEY OPINION LEADERS (KOL) IN CONSUMER BEHAVIOR IN LIVE STREAMING COMMERCE (LSC) - Aurida Mahelvi; Edwin Zusrony (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to see how much impact the variables attractiveness, expertise and trustworthiness have on the purchase interest of Shopee e-commerce. Data collection using questionnaires to obtain answers to research variables and respondent data. The sampling method uses convenience sampling techniques. The respondents of the study were all Millennials and Generation Z aged 18-37 years old Shopee e-marketplace users in Semarang City as many as 96 people. The questionnaire answer assessment indicator uses a 5-point Likert scale. The data analysis method uses multiple linear regression and is processed using SPSS software version 30. The results of the study show that the variables attractiveness, expertise and trustworthiness have a significant influence on purchase interest. The most dominant expertise variable in achieving optimal purchase interest in respondents is the Millennial generation and Generation Z aged 18-37 years old Shopee e-marketplace users in Semarang City.